1998
DOI: 10.1111/j.1439-0388.1998.tb00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance of dairy cattle at Asella livestock farm, Arsi, Ethiopia. I: Indigenous cows versus their F1 crosses

Abstract: Summary In this study the reproductive performance of indigenous Ethiopian cows and their F1 crosses was evaluated and factors affecting reproductive performance were assessed, based on crossbreeding data collected from Asella Livestock Farm, Ethiopia. Age at first calving, number of services per conception, days open, gestation length and calving interval were considered in the evaluation of reproductive performance. Results obtained showed that genetic (breed) group was a significant source of variation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
30
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 16 publications
11
30
4
Order By: Relevance
“…In contrast, the present study showed shorter postpartum estrus period compared to studies in Abernosa Ranch [25] and in small scale farms in and around Mekelle, Ethiopia [15]. In the present study, the calving interval was similar to previous reports [8,19]. In contrast, the present findings revealed shorter calving intervals compared to previous studies in central part of Ethiopia [6], Abernisa Ranch, Ethiopia [17], small scale dairy farms in and around Mekelle, Ethiopia [15], Malawi [22] and Tanzania [18].…”
Section: First Postpartum Estrus and Calving Intervalcontrasting
confidence: 54%
See 1 more Smart Citation
“…In contrast, the present study showed shorter postpartum estrus period compared to studies in Abernosa Ranch [25] and in small scale farms in and around Mekelle, Ethiopia [15]. In the present study, the calving interval was similar to previous reports [8,19]. In contrast, the present findings revealed shorter calving intervals compared to previous studies in central part of Ethiopia [6], Abernisa Ranch, Ethiopia [17], small scale dairy farms in and around Mekelle, Ethiopia [15], Malawi [22] and Tanzania [18].…”
Section: First Postpartum Estrus and Calving Intervalcontrasting
confidence: 54%
“…Further, comparable ages at first calving were recorded in previous studies in urban and in peri-urban crossbred dairy cattle farms, in central Tigray [16], and in crossbred cattle in Tanzania [17,18]. However, later age at first calving was recorded in the present study than in crossbred (Arsi breed X Jersey, and Arsi breed X Holstein Friesian) cattle in Asella, Ethiopia [19,20]. The current study showed comparatively earlier age in crossbred dairy heifers at first calving than in Zimbabwe [21], other parts of Ethiopia [6] and in Malawi [22].…”
Section: Age At First Service and Age At First Calvingcontrasting
confidence: 54%
“…Data collected for a long time on crossbreeding studies by different institutions has not been -E-mail: a.haile@cgiar.org systematically analyzed and documented to help in the design of sound and sustainable breeding program. Indeed, some studies compared indigenous cattle breeds with their contemporary crosses for dairy performance in Ethiopia (IAR, 1982;Kiwuwa et al, 1983;Haile-Mariam et al, 1993;Negussie et al, 1998;Demeke et al, 2004). Some workers (Haile-Mariam et al, 1993;Demeke et al, 2004) also estimated genetic parameters for the economic traits.…”
Section: Introductionmentioning
confidence: 99%
“…Abortion, infertility and sub-fertility are also some of the major problems recorded in many farms in urban and periurban areas in Ethiopia (Yoseph et al, 2003). Therefore, accurate evaluation of the reproductive efficiency of indigenous stocks and their crosses in different production systems is essential for the Original Research development of appropriate breeding strategies (Negussie et al, 1998).…”
Section: Introductionmentioning
confidence: 99%